An Inclusion Project of Collaborating Agrotourism and Performing Arts in Improving the Economy of the Setara Nanggalo Community - Nerosti; Zakaria, Farok; Hermansah; Eliza, Delfi; Efrianova , Vivi; Afriwan, Hendra (RUSAMILAE JOURNAL, 2025)
Nagari Setara Nanggalo, with its hilly geographical landscape, comprises 137,903 hectares of rice fields and 187 hectares of citrus agro-tourism that has been cultivated since 2015. However, since 2019 the orange yield has declined due to frequent flooding that damaged the crops. Apart from farming, the community is also actively engaged in traditional performing arts, where the development of Randai art, Salawat Dulang, and Ilau traditional dance originated. Through PPNB, a solution was introduced by integrating agro-tourism with performing arts, not only to serve as entertainment but also as a professional livelihood that strengthens the local economy, with farmers performing as professional paid artists when not working in the fields. This study involved three groups of respondents: (i) male farmers producing liquid organic fertilizer (POC), (ii) female farmers trained in embroidery, and (iii) teenagers offering packaged dance and Master of Ceremony (MC) services for weddings and events. Using the Participatory Rural Appraisal (PRA) method, the community actively engaged in problem-solving through group discussions and collaborative activities, which resulted in: (i) successful processing and distillation of Titonia leaves into liquid organic fertilizer by the male farmer groups, (ii) embroidery skills mastery among the women farmers/PKK group, and (iii) professional-level performance skills in Randai, dance, and MC services among the youth group. The findings show that all three groups achieved 100% skill proficiency in their respective fields, highlighting the potential of combining agriculture, tourism, and cultural arts as sustainable economic drivers for the community.